Dietary nutrients during gestation cause obesity and related metabolic changes by altering DNA methylation in the offspring - Bokor, Szilvia; Csölle, Ildikó; Felső, Regina; Vass, Réka A.; Funke, Simone; Ertl, Tibor; Molnár, Dénes (Frontiers in Endocrinology, 2024)
Growing evidence shows that maternal nutrition from preconception until lactation has an important effect on the development of non-communicable diseases in the offspring. Biological responses to environmental stress during pregnancy, including undernutrition or overnutrition of various nutrients, are transmitted in part by DNA methylation. The aim of the present narrative review is to summarize literature data on altered DNA methylation patterns caused by maternal macronutrient or vitamin intake and its association with offspring's phenotype (obesity and related metabolic changes). With our literature search, we found evidence for the association between alterations in DNA methylation pattern of different genes caused by maternal under-or overnutrition of several nutrients (protein, fructose, fat, vitamin D, methyl-group donor nutrients) during 3 critical periods of programming (preconception, pregnancy, lactation) and the development of obesity or related metabolic changes (glucose, insulin, lipid, leptin, adiponectin levels, blood pressure, non-alcoholic fatty liver disease) in offspring. The review highlights that maternal consumption of several nutrients could individually affect the development of offspring's obesity and related metabolic changes via alterations in DNA methylation.